Teachers’ Experiences with Students’ Learning Obstacles in Geometric Thinking: Insights from the van Hiele Framework - Nur'aini Muhassanah; Muhammad 'Azmi Nuha; Riski Aspriyani (International Journal of Research in Mathematics Education, 2025)
Understanding geometric concepts is often a challenge for students because it requires spatial thinking and deductive reasoning skills that develop gradually. This study aims to describe the barriers to student learning in geometric thinking based on teacher perceptions using van Hiele's theoretical framework. The research approach used was qualitative with a phenomenological design, involving 49 junior high school mathematics teachers from 35 schools across seven districts. Data were collected through questionnaires and in-depth interviews, then analyzed thematically. Interview data was collected from only six teachers selected through purposive sampling. The results of the study showed that students' learning barriers increased as their geometric thinking level increased. At level 0 (Visualization), the barriers were low (58.63%) because students were still able to recognize shapes visually. At level 1 (Analysis), the barriers increased to 64.61% (high category) because students had difficulty finding relationships between the properties of shapes. At level 2 (Informal Deduction), the barriers reached 72.48% (high category), especially in the use of formal mathematical language and the preparation of logical arguments. In addition, the results showed that epistemological barriers were related to weak mastery of basic concepts, ontological barriers were related to misclassification of geometric objects, and didactic barriers stemmed from external factors such as learning strategies and learning motivation. Overall, these results emphasize the need for contextual, tiered, and exploratory geometry learning designs to reduce learning barriers at every level of student thinking.